An assay of 4-hydroxy-trans-2-nonenal in human seminal plasma using a high-performance liquid chromatography with fluorescence detection - Drábková, Petra; Martínková, Jiřina; Míková, Veronika; Štramová, Xenie; Kanďár, Roman (University of Pardubice, 2012)
A method is described for the determination of 4-hydroxy-trans-2-nonenal in human seminal plasma. Semen samples were obtained from male partners of couples presenting for a fertility evaluation. After liquefaction, the samples were centrifuged and the seminal plasma was stored at –80 °C. 4-Hydroxy-trans-2- nonenal was derivatized with 1,3-cyclohexanedione to generate the fluorescent alkyl acridine derivative. After derivatization, seminal plasma proteins were precipitated with cold perchloric acid, and the supernatant was injected into the HPLC system. The separation was realized on an analytical reversed-phase column with fluorescence detection. The mixture of ethanol and deionized water was used as the mobile phase. The intra-assay coefficients of variation were below 10 %. Quantitative recoveries from spiked seminal plasma were between 62.0 and 81.0 %.